2014
DOI: 10.1002/ejic.201400123
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Controlled Metathesis Reactions of Methylruthenium(II) Complexes with Terminal Acetylenes

Abstract: Keywords: Reaction mechanisms / Metathesis / Ruthenium / Acetylenes / Methanol / Density functional calculationsWith the help of density functional theory (DFT) calculations, we theoretically investigated and rationalized the controlled metathesis reactions of methylruthenium complex trans-[Ru(CH 3 ) 2 (dmpe) 2 ] [dmpe = 1,2-bis(dimethylphosphanyl)ethane] (A) with terminal acetylenes. On the basis of the mechanistic study, two important issues related to the generation of mono-and bis-acetylido Ru complexes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…These results confirmed that the probe underwent a nucleophilic addition reaction with analyte. To validate the noncoplanar structure and the electronic behavior, we calculated the molecular structure with density functional theory (DFT). The molecule FHMI had a large planar conjugated structure in which the hydroxyl oxygen (donor), the ketonic oxygen (acceptor-2) as well as the positive nitrogen (acceptor-1) were included. When sensing HSO 3 – , FHMI was transformed to the product HHMI, forming a saturated hydroxyl oxygen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These results confirmed that the probe underwent a nucleophilic addition reaction with analyte. To validate the noncoplanar structure and the electronic behavior, we calculated the molecular structure with density functional theory (DFT). The molecule FHMI had a large planar conjugated structure in which the hydroxyl oxygen (donor), the ketonic oxygen (acceptor-2) as well as the positive nitrogen (acceptor-1) were included. When sensing HSO 3 – , FHMI was transformed to the product HHMI, forming a saturated hydroxyl oxygen.…”
Section: Results and Discussionmentioning
confidence: 99%